Modification Of The Granular Activated Carbon And Its Effect On Removal Of Cr(VI) From Aqueous Solution In Batch And Fixed-Bed Systems - Hassoon Ali, Ahmed; Ghali Attia, Hadi; Faisal Muhaisan, Farah (Journal of Engineering and Sustainable Development, 2014)
The adsorption processes of Cr(VI) from aqueous solution onto a granular activated carbon (GAC) and a modified granular activated carbon (MGAC) with AgNNO3, FeCL3 and Na2EDTA have been investigated. The surface characteristics of these activated carbons were measured. The results showed that the MGAC has a lower surface area and more active functional groups compared with the GAC. Adsorption parameters such as adsorbent dosage, pH of solution, temperature and contact time of the adsorption onto GAC and MGAC have been investigated in a batch adsorption experiments in order to obtain the optimum conditions for the Cr(VI) adsorption process. Thermodynamic modeling using temperatures studies was done to reveal the nature of adsorption which indicated that the process was spontaneous and physical in nature. Experimental equilibrium data have been obtained and correlated with Langmuir and Freundlich isotherms for the determination of the adsorption potential. The results have shown that the Langmuir isotherm model better fits the experimental data compared with the Freundlich isotherm for both GAC and MGAC. It was found that the MGAC has a higher Cr(VI) adsorption capacity (qm), with 11.082, 14.214, 25.842, 25.842 mg/g for GAC, (Ag+1-GAC), (Na+1-GAC) and (Fe+3-GAC) respectively. The breakthrough curves for the adsorption column test was obtained in a continuous adsorption fixed-bed experiment, The measured breakthrough times for GAC, (Ag+1-GAC), (Na+1-GAC) and (Fe+3-GAC) were found to be 10, 30, 40 and 60 min, respectively.